Development of a Model for the Acquisition and Assessment of Advanced Laparoscopic Suturing Skills Using an Automated Device. (June 2018) - Bilgic, Elif; Takao, Madoka; Kaneva, Pepa; Endo, Satoshi; Takao, Toshitatsu; Watanabe, Yusuke; McKendy, Katherine M.; Feldman, Liane S.; Vassiliou, Melina C.
Background . Needs assessment identified a gap regarding laparoscopic suturing skills targeted in simulation. This study collected validity evidence for an advanced laparoscopic suturing task using an Endo Stitch TM device. Methods . Experienced (ES) and novice surgeons (NS) performed continuous suturing after watching an instructional video. Scores were based on time and accuracy, and Global Operative Assessment of Laparoscopic Surgery. Data are shown as medians [25th-75th percentiles] (ES vs NS). Interrater reliability was calculated using intraclass correlation coefficients (confidence interval). Results . Seventeen participants were enrolled. Experienced surgeons had significantly greater task (980 [964-999] vs 666 [391-711], P = .0035) and Global Operative Assessment of Laparoscopic Surgery scores (25 [24-25] vs 14 [12-17], P = .0029). Interrater reliability for time and accuracy were 1.0 and 0.9 (0.74-0.96), respectively. All experienced surgeons agreed that the task was relevant to practice. Conclusion . This study provides validity evidence for the task as a measure of laparoscopic suturing skill using an automated suturing device. It could help trainees acquire the skills they need to better prepare for clinical learning.